Editor’s Editorial for HELTASA special issue - du Toit, Pieter (South African Journal of Higher Education, 2016)
As the title of this article suggests, the focus is on higher education seen as being framed differently and its response to the expectations of society at large. This contribution does not argue for a specific frame to be used. It rather serves as an editorial outer-frame for the individual inner-frames published in this edition – each article being a different frame designed, made, simple, ornate, wooden, golden leafed, etc. by an individual (author) or group (co-authors) of craftsmen and/or craftswomen. As higher education is multidimensional in all aspects, it is complex and each article can only offer a small ‘abstracted visual’ representation of the ‘bigger picture’ (what we currently know) of the higher education world and the world of society in which it exists. Some articles are framed as still lives, some as landscapes, others as portraits, etc. – you decide. My article, as the outer-frame, has as aim the initiating of scholarly discourse on the views we are offered to see through the different frames with a view to inviting the reader to engage the discourse – appreciating what is offered as a painting, other fine art, digital image, quilt, etc. I draw on the work of several authors that we consider scholars of mainly learning and teaching in its widest sense, and scholars of leadership in and of higher education within a societal perspective to underpin our discourse. The line of thought is guided by some keywords found as part of the abstract to each article.